Academic Industry Collaboration and Islamic Finance Support: Evidence from Halal Business Incubators and Student Entrepreneurship - Rahmawati, Rahmawati; Putri, Juliana; Badriah, Badriah (IQTISHADIA, 2026)
This study examines how working with businesses and using Islamic finance can help students succeed in starting their own businesses through halal business incubation. Universities are becoming important in helping students start businesses, especially in places that follow Sharia law. This study used surveys from 200 student entrepreneurs in a halal business incubator at a university in Aceh, Indonesia. The data were analyzed using PLS-SEM. The study found that halal business incubators greatly help students improve their business skills. Islamic finance improves the functioning of incubators and directly helps students succeed in business. Working with businesses also directly helps students, but it does not help much through incubators. This suggests that other methods, such as learning by doing and working with professionals, might be important. The study shows how working with businesses and using Islamic finance can help in halal business environments. The findings are helpful to universities, policymakers, and Islamic financial institutions in improving their support for Sharia-compliant entrepreneurship.